2016
DOI: 10.1371/journal.pone.0156258
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Health-Related Quality of Life among Tuberculosis Patients in Two Cities in Yemen

Abstract: BackgroundThe health-related quality of life (HRQoL) of Tuberculosis (TB) patients is important because it directly influences the outcome of TB patients in several aspects. The current study aims to evaluate and to find the factors influencing the HRQoL of TB patients in two major TB-prevalent cities (Taiz and Alhodidah) in Yemen.MethodsA prospective study was conducted, and all TB patients meeting the HRQoL criteria were asked to complete the HRQoL SF-36 survey. The records of TB patients were examined for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 54 publications
4
48
0
5
Order By: Relevance
“…Study of Uganda shows older men had lower HRQoL score where as women had higher HRQoL as similar to this study [9]. The health-related quality of life (HRQoL) of Tuberculosis (TB) patients of Yemen was similar to this study, HRQoL of measurement by SF-36 of 197 found that the mean PCS and MCS scores at the early treatment were low this is the poor health condition [10].…”
Section: Discussionsupporting
confidence: 83%
“…Study of Uganda shows older men had lower HRQoL score where as women had higher HRQoL as similar to this study [9]. The health-related quality of life (HRQoL) of Tuberculosis (TB) patients of Yemen was similar to this study, HRQoL of measurement by SF-36 of 197 found that the mean PCS and MCS scores at the early treatment were low this is the poor health condition [10].…”
Section: Discussionsupporting
confidence: 83%
“…Approximately 30.8% of defaulters reported stigmatization from society, friends and culture as their main reason for defaulting. A recent study also strongly related TB to stigmatization in Yemen . In Yemen, a TB infection creates numerous troubles in society due to stigmatization.…”
Section: Discussionmentioning
confidence: 94%
“…The results show that living in rural areas is a main risk factor associated with TB treatment defaulting. The majority of TB patients travel from rural areas to urban areas for proper diagnosis and treatment due to the shortage of laboratory and health facilities in rural areas . This high percentage of defaulters from rural areas can be due to the poor economic situation in these areas and the low education level of defaulters from these areas .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HRQOL scoring was sensitive to changes in the quality of life of patients as demonstrated by statistically significant differences in physical and mental component scoring observed among the patients. Several studies reported that quality of life of patients with tuberculosis is negatively affected [12][13][14] .…”
Section: Resultsmentioning
confidence: 99%